Clinical reasoning for performance of transesophageal echocardiography in veterans with Staphylococcus aureus bacteremia - Emily C. Woods; Trisha S. M. Nakasone; Cybele A. Renault (Cambridge University Press, 2023)
This study examined physicians' reasoning about obtaining transesophageal echocardiography (TEE) in cases of Staphylococcus aureus bacteremia (SAB). In 221 cases of SAB over 5 years, the most common reasons for not performing TEE were clinical response to antibiotics, negative TTE results, and the expectation that TEE would not change management.